Initiating Mosque-Based Social Entrepreneurship through Participatory Action Research: Implications for Community Social Work - Noorkamilah; Nurul Fajriyah Prahastuti; Lathiful Khuluq; Abidah Muflihati (UIN Sunan Kalijaga Yogyakarta, 2026)
This study investigates the initiation of mosque-based social entrepreneurship through the SM Klin program and its implications for community social work. Employing a two-cycle Participatory Action Research (PAR) design guided by the Look-Think-Act framework, the study involved 19 core participants representing mosque management, local leadership, and a women’s religious study group. Data were collected through participant observation, transect walks, in-depth interviews, focus group discussions, and document analysis, and were thematically analyzed across four dimensions of social entrepreneurship: social value, civil society, social innovation, and economic activity. The first cycle generated awareness, basic skills, and initial production experience but also revealed technical failures. Collective reflection during the second cycle led to improvements in equipment and procedures, clearer task allocation, business management training, the creation of the SM Klin brand, and the establishment of a preliminary margin-sharing scheme. Social value was demonstrated through increased skills, self-confidence, cooperation, and women’s participation. The primary innovation involved transforming mosque funds, legitimacy, and community networks into a collective enterprise mechanism. However, governance arrangements, ownership rights, legal compliance, financial record-keeping, and market sustainability remained underdeveloped. The study concludes that SM Klin reached the stage of an emerging social venture rather than a financially sustainable enterprise with demonstrated welfare impacts. These findings underscore the role of PAR in facilitating collective learning, mobilizing local assets, and strengthening community capacity. Keywords: social entrepreneurship, mosque, participatory action research, women’s empowerment, community social work Penelitian ini menganalisis proses perintisan kewirausahaan sosial berbasis masjid melalui program SM Klin serta implikasinya bagi pekerjaan sosial komunitas. Penelitian menggunakan Participatory Action Research dengan dua siklus Look-Think-Act yang melibatkan 19 partisipan inti dari unsur takmir masjid, tokoh masyarakat, dan kelompok pengajian perempuan. Data dikumpulkan melalui observasi partisipatif, transek, wawancara mendalam, diskusi kelompok terarah, dan dokumentasi, kemudian dianalisis secara tematik berdasarkan empat dimensi kewirausahaan sosial: nilai sosial, masyarakat sipil, inovasi sosial, dan aktivitas ekonomi. Hasil penelitian menunjukkan bahwa siklus pertama menghasilkan kesadaran, keterampilan dasar, dan pengalaman produksi awal, tetapi masih diwarnai kegagalan teknis. Refleksi bersama pada siklus kedua mendorong perbaikan alat dan prosedur, peningkatan pembagian kerja, pelatihan pengelolaan usaha, pembentukan merek SM Klin, dan penyusunan skema awal pembagian margin. Nilai sosial tampak pada peningkatan keterampilan, kepercayaan diri, kerja sama, dan partisipasi perempuan. Inovasi utama terletak pada pengubahan dana serta jaringan masjid menjadi mekanisme usaha kolektif. Namun, tata kelola, kepemilikan, legalitas, pencatatan keuangan, dan keberlanjutan pasar belum terbentuk secara memadai. Penelitian menyimpulkan bahwa SM Klin telah mencapai tahap perintisan usaha sosial, bukan usaha yang telah terbukti meningkatkan kesejahteraan ekonomi. Temuan ini menegaskan pentingnya PAR dalam memfasilitasi pembelajaran kolektif, mobilisasi aset lokal, dan penguatan kapasitas komunitas. Kata kunci: kewirausahaan sosial; masjid; riset aksi partisipatif; pemberdayaan perempuan; pekerjaan sosial komunitas